Determining evacuation directions for use in Dynamic Signage System of evacuation routes - Barański, Mariusz; Brzezińska, Dorota; Haznar-Barańska, Agnieszka; Barański, Dawid (Instal, 2023)
In the article, the authors present the results of model tests indicating the need for evacuation guidance systems to improve evacuation safety. The architecture of traffic routes and the internal layout of obstacles in the building mean that conducting evacuation in a safe manner is not synonymous with conducting it by the shortest possible route. This is particularly noticeable when there is a danger on the shortest possible evacuation route for the user. Analyses for design fires regardless of the speed of their development have shown that optimized evacuation signage dependent on the location of the danger leads to a safer way of conducting it, without unnecessarily exposing users to dangerous factors of the fire. On the other hand, as the speed of fire development increases, the level of safety increases with optimized signage. The study also proved the effectiveness of the model of the relative length of the escape route to emergency exits. The present research is an extension of the analysis conducted by Choi and Chi, which used graph theory and the risk of smoke exposure for users moving along different sections of the escape route.
Keywords: fire protection systems; evacuation lighting; evacuation signage; evacuation management